Benarkah Empati Mempengaruhi Pemaafan Pada Mahasiswa? - Netty Widiastuti; Kondang Budiyani (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2026)
Background: College students are exposed to diverse interpersonal dynamics that may give rise to conflict and emotional distress. Such conditions can trigger anger, withdrawal, or retaliatory impulses. Forgiveness is considered one way to reduce the negative impact of conflict, while empathy is believed to play a role in helping individuals understand the perspectives of others. Objective: This study aimed to examine the relationship between empathy and forgiveness among college students. Method: The study involved 100 students, (50 males and 50 females). Forgiveness was measured using the Transgression-Related Interpersonal Motivation Scale (α = 0.913), while empathy was assessed using the Interpersonal Reactivity Index (α = 0.820). The data were analyzed using Pearson’s Product-Moment correlation. Result: The analysis revealed a correlation coefficient = −0.041, with p = 0.344 (p > 0.05), indicating that there was no significant positive relationship between empathy and forgiveness among students. Conclusion: Empathy was not found to be significantly associated with forgiveness. These findings suggest that forgiveness is influenced by other factors beyond empathy, such as emotion regulation, psychological maturity, and personal values. Therefore, intervention programs in university settings should focus not only on enhancing empathy but also on strengthening emotional regulation, conflict resolution, and psychological resilience.